(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Bats (Chiroptera) are reservoirs for zoonotic diseases, including Rabies, Hendra, Nipah, SARS-CoV, Ebola virus. Hence their importance as a potential reservoir hosts of viruses affecting human and animal health. In our country, there is no knowledge of bats as reservoir for viruses except rabies. The aim of this investigation was the molecular characterization of rabies virus and other viral agents, isolated from bats in Venezuela. The molecular characterization was based on: viruses with impact in public health, persistence in hosts and endemic areas. A total of 54 bats were collected in different states and years. Those were identified and classified into: 12 vampires, 29 frugivorous and 13 insectivorous belonging to different families, genera and species. They were autopsied to collect tissues from different organs including brain tissue of livestock positive to rabies virus. Different systems were used for PCR to detect DNA and RNA viral genomes. Samples were amplified, molecularly characterized and sequenced to identify the phylogeny of each virus. We were able to detect 8 Herpesviruses and 4 Polyomaviruses in trachea and lungs samples from different bat species and one Astroviruses in an intestine of an insectivorous bat. Eight Rabies isolates were grouped in the genus Lyssavirus genotype 1. Four of them characterized as antigenic variant 3 (Desmodus rotundus). The detection of these viral agents in the Venezuelan bats is the first and paramount information for the study of these unknown agents, which could pose great risk to humans and livestock health in our country.